Teachers’ Efforts to Overcome Student Learning Style Problems in Social Studies Subjects at Tondano 2 The State Middle School, Minahasa Regency - Korompis, Manuel E.; Karwur, Hermon Maurits; Tuerah, Paulus Robert; Sulistyosari, Yunike; Mesra, Romi; Wahani, Christian J.; Rahman, Rahmania (Technium Social Sciences Journal, 2023)
This article aims to explore problems, attempt to overcome them, and identify supporting and inhibiting factors related to student learning styles in social studies at SMP Negeri 2 Tondano. The approach used is qualitative, where the researcher is the key instrument, using purposive sampling and snowball techniques, survey techniques with triangulation (combined). Data collection techniques using interviews, observation (observations), documents, and literature. Researchers used the Miles and Huberman qualitative data analysis technique. Activities in data analysis, namely data reduction, data display, and conclusion drawing/verification. The results show that there are several learning style problems among students in social studies learning at SMP Negeri 2 Tondano. While the efforts made by the teacher in overcoming the problem of learning styles include: the teacher tries to understand student characteristics, understands student potential, develops innovative learning models, recognizes student learning styles, develops interest in learning, uses innovative media, provides motivation, involves students in discussions and provides explanations . Supporting factors in overcoming the problem of learning styles among students at SMP Negeri 2 Tondano, which include; the enthusiasm of students in learning. There is a teacher’s enthusiasm in learning, there is a passion to succeed in learning. The inhibiting factors in overcoming learning style problems among students at SMP Negeri 2 Tondano include several things such as; there is still a lack of student creativity, lack of motivation to learn, limited school learning facilities.